SISTEM PENGENDALIAN INTERN PENJUALAN KREDIT PADA PT XYZ - Alcianno G. Gani (JURNAL MITRA MANAJEMEN, 2021)
ABSTRACTPT. XYZ is a manufacturing company that processes plastic raw materials into toy products, the company has been running since 2015, in an effort to make the company a better direction, management develops companies with a computerized accounting recording system. In a credit sales system that has a greater risk level than cash sales, PT XYZ requires a good internal control system. This study aims to determine the procedures that form a credit sales system and determine whether the internal control system has been implemented in the company. The type of data used in this research is primary data and secondary data which are collected through documentation and literature. From the results of the evaluation, it was found that the PT XYZ timber company credit sales system procedure was not good because sometimes receiving orders used personal email from Marketing. The internal control system implemented at PT. XYZ has not been carried out well, these deficiencies can be seen in the concurrent duties section, as well as the absence of credit and billing sections and forms used by the company, even though there is document numbering but it is still in the interests of each section, so document accountability is difficult to trace. Keywords: Credit Sales Procedure, Internal Control System.